Pengaruh Aplikasi Mikoriza Arbuskular dan Media Tanam Terhadap Pertumbuhan Kelapa Bido di Kebun Rehabilitasi - Himawan Bayu Aji; Suryati Tjokrodiningrat; Wawan Sulistiono (Jurnal Pertanian Khairun, 2022)
The North Maluku region is famous for its agricultural sector, sub-sector of coconut plantations. However, there are various problems that become challenges in efforts to increase coconut production in North Maluku. The purpose of the study was to obtain information on morphological characteristics and growth related to the dose of arbuscular mycorrhizal fungi and the composition of the growing media. The research was conducted at the North Maluku Plantation (BPTP) from August 2019 to February 2020. The study used a factorial of 2 factors, namely the dose of JMA and the composition of the growing media. The first factor is the dose of JMA which consists of 3 levels of M1 (2g); M2 (4g); and M3 (6g). The second factor is a combination of 3 levels of planting media; manure (PK): sawdust (SG): sand (Ps). Data were analyzed using variance (analysis of variance). The results showed that the combination of treatment with a dose of JMA and a certain planting media could stimulate the growth of plant height, stem circumference, number of variables, and the highest crown length at the age of 6 bst.Keywords: bido coconut, arbuscular mycorrhizal fungi, growing media, morphological and growth characteristics